The Existence of Akonipuk and the Role of Christian Education in Educating the Hubula Community in Balim Valley Wamena Papua - Elys Lusiari Papuana Toam; Demsy Jura (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The Existence of Akonipuk and the Role of Christian Education in Educating the Hubula Community in Balim Valley Wamena Papua is a cultural study from the perspective of Christian Education. The effort is aimed at educating the community so they can make informed choices and attitudes regarding the cultural beliefs associated with Akonipuk. Indonesia, as one of the countries rich in culture and diversity, has brought its existence on the international stage as one of the largest multicultural countries in the world. This article highlights the presence of Akonipuk in the lives of the Hubala community in the Balim Valley of Wamena Papua and the perspective of Christian education regarding its existence in educating the community. It is hoped that through this study, the people in that area will have a correct understanding and be able to appropriately situate the cultural aspects related to Akonipuk within the culture of the Christian community. The research approach employed is descriptive qualitative.